(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Vanadium is a ubiquitous transition metal that has been generating contrasting research interest. Therapeutically, vanadium possess antidiabetic, antitumor, antiparasitic and even neuroprotective activities. On the flip side, vanadium has been reported to cause multisystemic toxicities with a strong predilection for the nervous system. Despite several reports on potential benefits of low-dose vanadium (LDV) and toxic effects of high-dose vanadium (HDV), there are no comparative studies done thus far. This study therefore explored the comparative effects of LDV and HDV exposure in mice during postnatal development. A total of nine (9) nursing mice were used in this study; with three nursing mice and their pups (n = 12 pups per group) randomly assigned to each of the three test groups. The nursing dam were given intraperitoneal (i.p) injection of vanadium at 0.15mg/kg and 3mg/kg for LDV and HDV respectively, and subseqently to the pups from postnatal day (PND) 15 till sacrifice on PND 90. We discovered that neurodevelopmental motor function test of mice-pups exposed to LDV here showed improved motor development, muscular strength and memory capacities whereas HDV led to motor function impairment, reduced muscular strength and memory capacities. LDV-exposed mice showed mild histological lesions in cerebral cortex whereas high-dose showed distinct histological lesions in different parts of the brain ranging from cerebellar Purkinje neuronal pathology (central chromatolysis), pyramidal neuronal loss in CA1 region, architectural distortion as well as fewer neurons in olfactory bulb. We saw mild lesions with LDV in both liver and kidney, however, with HDV exposure, there was diffuse hepatocellular vacuolar degeneration and congestion of blood vessels in liver, shrinkage of renal glomerulus and degenerated epithelial cells of kidney. Conclusively, beneficial effect of vanadium is proven as it facilitated body weight gain which translate in organ weight at low-dose, while high-dose caused decreased neurobehaviour and histological lesions.